Recovery of Antimicrobials and Bioaccessible Isoflavones and Phenolics from Soybean (Glycine max) Meal by Aqueous Extraction - Cyntia S. Freitas; Genilton Alves da Silva; Daniel Perrone; Mauricio A. Vericimo; Diego dos S. Baião; Patrícia R. Pereira; Vânia M. F. Paschoalin; Eduardo M. Del Aguila (Molecules, 2018)
Soybeans display strategic potential in food security as a source of protein and functional bioactives for human consumption. Polyphenols and other bioactive compounds can be recovered after an aqueous extraction from soybean meal, a byproduct of soy oil refining. The objective of the present study was to compile and quantify compounds from soybean oil refinery by-products, providing information about valuable bioactive phytochemicals, their bioaccessibility and potential bioactivities. Genistin, daidzin, glycitin and malonylgenistin were the predominant isoflavones, and the overall bioaccessibility of their glycosidic forms was of nearly 75%. Sixteen phenolics were identified and caffeic acid, 5-caffeoylquinic chlorogenic acid and hesperidin were the most predominant. Approximately 30% of gallic acid, syringic acid, vanillic acid and myricetin were released and the antioxidant capacity of aqueous extract was enhanced after simulated in vitro gastro intestinal digestion. The ability of aqueous soybean meal extract to inhibit lipid peroxidation was higher than natural and synthetic food antioxidants. Antimicrobial activity against several foodborne pathogens and antitumoral activity towards human glioblastoma cell line were also observed, but the aqueous extract showed no cytotoxicity to healthy murine cells. Compounds derived from the aqueous soybean meal extract have the potential to be used as health promoting agents.